The Challenges of A Developmental Local Government in Municipal Service Delivery: The Case of Vhembe District Municipality, South Africa - Nghonyama, Goodman; Sethu, Mahlodi Joyce; Mafunisa, John Mutuwafhethu (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2025)
This study focuses on probing the challenges of Developmental Local Government in Municipal service delivery within Vhembe District Municipality. The study further argues that despite the vital role in promoting the socio-economic needs of the communities through local community engagement in the municipality, the Developmental Local Government is challenged with, among other problems, maladministration and corruption. Developmental local governance, also known as local governance for development, aims to improve the future of communities by promoting local socio-economic development programs and projects. This study advocates for a qualitative approach to probe the impediments. The study reveals that various encounters contribute to the challenges of Developmental local government in municipal service delivery in the Vhembe district municipality. To deal with the impediments of municipal service delivery in developmental local government, there is a need for the municipality to foster public accountability. It is therefore recommended that, to ensure capacity building for effective service provision, good governance needs to be ensured. From conclusions drawn from key findings, it is argued that the enhancement of community participation, provision of education and training to municipal employees, has to be implemented through municipal policies.